Penentuan Kabupaten/Kota Terbaik Dalam Produksi Sapi Potong di Provinsi Sumatera Selatan Melalui Analisis Kuadran - Nursanty Nursanty; Hendrixon Hendrixon (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Nursanty N, Hendrixon H. 2020. Determination of the best districts/cities in beef cattle production in South Sumatra province through quadrant analysis. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Beef is one of the commodities needed to meet protein needs, because it contains high-quality protein. As the increasing rate increases, the higher the speed of beef production. The purpose of this study was to determine the appropriate area for the development of beef cattle by looking at the growth rate of beef cattle in South Sumatra Province in 2015 until 2017. The data source was obtained from the Central Statistics Agency. Based on regression analysis, the participation rate is very small on the rate of beef cattle production in South Sumatra Province. The results of the quadrant analysis resulted in four groups of surrounding areas that have low and high populations, regions that have low populations and low production, areas that have large numbers and low production with areas that have high and high populations. The feasible area for the development of beef cattle is the city of Palembang and Lubuk Linggau City, where through quadrant analysis this area has the most potential to have small quantities but has very high production. The city of Palembang has an average population of 7,858.67 tails with an average production of 1, 769,404.52 Kg and Pagaralam City 1,085 with an average production of 421,533.14 Kg.